Tinjauan Hukum Pelaksanaan Gadai Kebun Cengkeh di Desa Diule Kecamatan Tolitoli Utara Kabupaten Tolitoli - Ahmad Malontu (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the mechanism of implementation of the clove garden pawn and the legal consequences for the owner of the upper clove garden which was pawned in Diule Village, North Tolitoli District, Tolitoli Regency. Research data were collected through interviews and observations, analyzed using descriptive analytical techniques with an inductive mindset. The results of the study concluded that the practice of pawning clove gardens that occurred in Diule Village was seen to be very detrimental to the clove garden owners, because of the urgency of the need for money, the applicant pawned his clove garden so that they were bound to loan sharks who acted as money lenders. This research is a field research where data collection is done by interviewing informants. In addition, the author also conducts document study research through data and books related to the research topic. Furthermore, the data obtained were analyzed qualitatively and presented descriptively. Based on the analysis, the authors conclude several things, including: 1. The form and process of the implementation of the clove garden pawn in Diule Village, North Tolitoli District, Tolitoli Regency still uses a long-standing habit of pawning clove gardens orally without any time limit for redemption. mortgaged land. 2. Efforts to overcome losses, namely the provisions in article 7 paragraph (1) of Law no. 56 Prp 1960 which obliges the pawnbroker to return the pawned land to the pawnee one month after the crops are harvested, without any ransom.